2012
DOI: 10.1186/1475-9276-11-3
|View full text |Cite
|
Sign up to set email alerts
|

A multilevel analysis of social capital and self-reported health: evidence from Seoul, South Korea

Abstract: BackgroundThis study aims to resolve two limitations of previous studies. First, as only a few studies examining social capital have been conducted in non-western countries, it is inconclusive that the concept, which has been developed in Western societies, applies similarly to an Asian context. Second, this study considers social capital at the individual-level, area-level and cross-levels of interaction and examines its associations with health while simultaneously controlling for various confounders at both… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 58 publications
1
18
0
Order By: Relevance
“…Our results are in accordance with earlier studies in which researchers proved the relationships between social activity and health status (Uphoff et al, 2013;Han et al, 2012;Shöllgen, 2011;Vonneilich, 2012). The results showed that health is closely correlated with health status and the intervention to improve it should concentrate on social activity and social participation, like health intervention in team where people can change their opinions and ideas thanks to each others.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Our results are in accordance with earlier studies in which researchers proved the relationships between social activity and health status (Uphoff et al, 2013;Han et al, 2012;Shöllgen, 2011;Vonneilich, 2012). The results showed that health is closely correlated with health status and the intervention to improve it should concentrate on social activity and social participation, like health intervention in team where people can change their opinions and ideas thanks to each others.…”
Section: Discussionsupporting
confidence: 92%
“…We need to analyse them with the help of the following environmental factors: social situation, income status, and level of education. The social capital can affect the health condition, but it can apply also the other way aroundthat is why we need to be careful with the data or examine it with longitudinal research (Han et al, 2012). In our study we considered to social capital at individual level, highlighting person's social participation.…”
Section: Social Capital and Social Participationmentioning
confidence: 99%
“…There is evidence that neighborhood psycho-social characteristics can mediate the adverse effect of having a chronic disease and attenuate the impact of such conditions on poor self-rated health 53 . A number of studies report significant effects of environmental, social and physical contextual characteristics being perceived as potential mediators in the association mechanism between contextual socioeconomic characteristics and self-rated health 34,37,43,54 .…”
Section: Discussionmentioning
confidence: 99%
“…Even when different socioeconomic indicators are applied, areas that are more deprived, less affluent or with greater income inequalities return higher percentages of individuals with poor self-rated health 29,30,31,32 . Physical, environmental characteristics (signs of physical disorder such as graffiti, poor public lighting, waste accumulated in the streets) 33,34,35 and psycho-social features (social capital) 36,37 , collective efficacy 38 or social cohesion 34 also display an association with self-rated health, although of a lesser magnitude than socioeconomic indicators 39,40 . In England and Scotland, physical, social and political aspects of the environment (such as high levels of unemployment, low access to private transport, poor quality of the physical environment and low levels of political engagement) were all associated with worse self-rated health 38 .…”
Section: Analyzing Data From Risk and Protective Factors Surveillanmentioning
confidence: 99%
“…A few of these studies have also been conducted in low and middle income countries and very few in sub-Saharan Africa [11]–[13]. This lack of information presents a serious challenge to the expansion of the beneficial effects of social capital on health as implied in various studies [14][16]. It is thus very important to have evidence of social relations and their effect on health in sub-Saharan African countries, to inform decision making, resource allocation and priority setting for healthcare interventions.…”
Section: Introductionmentioning
confidence: 99%